Beyond the Immune Suppression: The Immunotherapy in Prostate Cancer. (16th June 2015) - Silvestri, Ida; Cattarino, Susanna; Aglianò, Anna Maria; Collalti, Giulia; Sciarra, Alessandro
Abstract : Prostate cancer (PCa) is the second most common cancer in men. As well in many other human cancers, inflammation and immune suppression have an important role in their development. We briefly describe the host components that interact with the tumor to generate an immune suppressive environment involved in PCa promotion and progression. Different tools provide to overcome the mechanisms of immunosuppression including vaccines and immune checkpoint blockades. With regard to this, we report results of most recent clinical trials investigating immunotherapy in metastatic PCa (Sipuleucel-T, ipilimumab, tasquinimod, Prostvac-VF, and GVAX) and provide possible future perspectives combining the immunotherapy to the traditional therapies.